HR Management Transformation in Indonesia MSMEs: The Role of AI in SOP Making and Recruitment - Wulandari, Astri; Diko, M. Attila Ibest Moeslem J. (Journal of Ecohumanism, 2024)
This study explores the influence of Artificial Intelligence (AI) on Human Resource management practices in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, with a special focus on the efficiency of creating Standard Operating Procedures (SOPs) and recruitment processes. Using a quantitative approach and Structural Equation Modeling (SEM) through SMART PLS, data was collected from 307 MSMEs that have adopted AI. The results of the study show that AI significantly improves SOP creation and recruitment efficiency, which has a positive impact on the overall performance of MSMEs. However, challenges such as resource limitations and potential bias in AI systems also need to be considered. These findings suggest that the adoption of AI in MSMEs can drive substantial operational improvements. This research provides valuable insights for MSMEs looking to leverage AI to gain a competitive advantage and emphasizes the need for AI solutions tailored to the needs of this sector.